Auxin polar transport in stamen formation and development: how many actors? - Cardarelli, Maura; Cecchetti, Valentina (Frontiers in Plant Science, 2014)
In flowering plants, proper development of stamens, the male reproductive organs, is required for successful sexual reproduction. In Arabidopsis thaliana normally six stamen primordia arise in the third whorl of floral organs and subsequently differentiate into stamen filaments and anthers, where male meiosis occurs, thus ending the early developmental phase. This early phase is followed by a late developmental phase, which consists of a rapid elongation of stamen filaments coordinated with anther dehiscence and pollen maturation, and terminates with mature pollen grain release at anthesis. Increasing evidence suggests that auxin transport is necessary for both early and late phases of stamen development. It has been shown that different members of PIN (PIN-FORMED) family are involved in the early phase, whereas members of both PIN and P-glycoproteins of the ABCB (PGP) transporter families are required during the late developmental phase. In this review we provide an overview of the increasing knowledge on auxin transporters involved in Arabidopsis stamen formation and development and we discuss their role and functional conservation across plant species.